Antioxidant activities of purified glycoprotein extracted from Codium decorticatum - Dharmaraj Senthilkumar, Sivaraman Jayanthi (Journal of Applied Pharmaceutical Science, 2015)
Marine algae are known to produce an extensive variety of bioactive metabolites and several novel drugs have been derived for the pharmaceutical industries. However glycoproteins from the algae have not been adequately explored for their potential as a source of bioactive substances. The objectives of this study were to investigate the antioxidant activity effect of glycoprotein (GLP). In the experiment of the radical elimination ability by means of 1,1-diphenyl-2-picryhydrazyl (DPPH) expressed anti-oxidative effect depending on the concentration considering GLP. Hydroxyl (OH) radical, superoxide radical (O2) and nitric oxide radial (NO) scavenging also showed that antioxidant abilities in the dose depended concentration. These results express that GLP eliminates reactive oxygen species (ROS), protect cell membrane, and can act as antioxidants. Therefore, it is thought that GLP can be used to new material of food supplements related to antioxidants.
Keywords: Glycoprotein, Antioxidant activity, Green algae, DPPH, Reducing power, Codium decorticatum.